RETRACTED ARTICLE: Long noncoding RNA LINC-PINT inhibits non-small cell lung cancer progression through sponging miR-218-5p/PDCD4 - Libin Zhang; Jing Hu; Jiagui Li; Qiuju Yang; Menghui Hao; Liang Bu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We, the Editors and Publisher of Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Zhang, L., Hu, J., Li, J., Yang, Q., Hao, M., & Bu, L. (2019). Long noncoding RNA LINC-PINT inhibits non-small cell lung cancer progression through sponging miR-218-5p/PDCD4. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 1595–1602. https://doi.org/10.1080/21691401.2019.1605371Since publication, concerns were identified regarding the integrity of the Quantitative RT-PCR methodology and reported results in the article. When approached for an explanation, the authors responded, however, they were unable to address the concerns raised. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding authors have been informed.We have been informed in our decision-making by our editorial policies and the COPE guidelines.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.